Dinâmica do fósforo no solo e a implementação de fertilizantes organominerais bioativos - Souza, Mariana (Universidade Federal de São Carlos, 2026)
Brazil is a major importer of mineral fertilizers; however, given the global challenges, there is a growing need to develop a domestic market. This study addresses the economic and environmental issues associated with the excessive use of these fertilizers and the industrialization of agriculture. In this context, the development of modern fertilizers with microbiological and organic applications has contributed to increasing nutrient absorption efficiency and promoting sustainability. The dynamics of phosphorus in the soil directly influence its availability; therefore, strategies that increase nutrient availability to plants are necessary. In this context, slow-release fertilizers have become a promising alternative, enhancing nutrient uptake throughout the crop life cycle and enabling the replacement, even if only partially, of traditional fertilizers. An example of these inputs is the bioactive organomineral fertilizer, which provides nutrition through the combination of organic and mineral components, in addition to microbiological activation by fungi and bacteria. This product still requires further improvements; however, it has gained increasing visibility due to its ability to reuse agro-industrial waste, contributing to a circular economy.
Phosphorus dynamics in soil and the implementation of bioactive organomineral fertilizers
Keywords: organominerais; fósforo; adsorção no solo; fertilizantes; microrganismos; CIENCIAS EXATAS E DA TERRA::QUIMICA; 1. Erradicação da Pobreza; 2. Fome Zero e Agricultura Sustentável; 13. Ação contra a Mudança Global do Clima